Effects of 4‐Br‐A23187 on Bacillus subtilis cells and unilamellar vesicles reveal it to be a potent copper ionophore. Issue 17 (27th June 2022) - Senges, Christoph H. R.; Warmuth, Helen L.; Vázquez‐Hernández, Melissa; Uzun, Huriye Deniz; Sagurna, Leonie; Dietze, Pascal; Schmidt, Claudia; Mücher, Brix; Herlitze, Stefan; Krämer, Ute; Ott, Ingo; Günther Pomorski, Thomas; et al.
Abstract: Ionophores are small molecules or peptides that transport metal ions across biological membranes. Their transport capabilities are typically characterized in vitro using vesicles and single ion species. It is difficult to infer from these data which effects ionophores have on living cells in a complex environment (e.g., culture medium), since net ion movement is influenced by many factors including ion composition of the medium, concentration gradients, pH gradient, and protein‐mediated transport processes across the membrane. To gain insights into the antibacterial mechanism of action of the semisynthetic polyether ionophore 4‐Br‐A23187, known to efficiently transport zinc and manganese in vitro, we investigated its effects on the gram‐positive model organism Bacillus subtilis . In addition to monitoring cellular ion concentrations, the physiological impact of treatment was assessed on the proteome level. 4‐Br‐A23187 treatment resulted in an increase in intracellular copper levels, the extent of which depended on the copper concentration of the medium. Effects of copper accumulation mirrored by the proteomic response included oxidative stress, disturbance of proteostasis, metal and sulfur homeostasis. The antibiotic effect of 4‐Br‐A23187 is further aggravated by a decrease in intracellular manganese and magnesium. A liposome model confirmed that 4‐Br‐A23187 acts as copper ionophore in vitro.